2020
DOI: 10.1007/s42452-020-03884-8
|View full text |Cite
|
Sign up to set email alerts
|

Usage of Ti-surface-modified filler material to increase the joint strength of High-Strength Low Alloyed (HSLA) steels under different load types

Abstract: Welding-related loss of strength, especially in the case of fatigue, significantly reduces the range of applications for high-strength fine-grained structural steels. In order to counteract this situation, the aim of the work is to increase the strength of welded joints made of high-strength fine-grained structural steels by using coated welding consumables. This is described using the example of a titanium coating for quasi-static and abrupt dynamic load and fatigue. The thermomechanical rolled fine-grained s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In addition, grain boundary ferrite is formed for higher joining energy levels. The found microstructure is typical for this type of filler metal 26 , 33 . For lower energy levels, a slight decrease in grain size can be anticipated, which is also a typical phenomenon for this type of filler.…”
Section: Experimental Procedures and Resultsmentioning
confidence: 62%
“…In addition, grain boundary ferrite is formed for higher joining energy levels. The found microstructure is typical for this type of filler metal 26 , 33 . For lower energy levels, a slight decrease in grain size can be anticipated, which is also a typical phenomenon for this type of filler.…”
Section: Experimental Procedures and Resultsmentioning
confidence: 62%
“…For the development of an alternative alloying concept, it has already been proven by preliminary investigations that a change in the mechanical properties occurs through the application of thin-film coatings on solid wire surfaces. Furthermore, it was shown that an influence on the process properties is caused by the alloying elements present on the surface [16][17][18][19][20][21][22]. In addition, an influence on the process properties and explicitly on the characteristics of the welding arc was recognized.…”
Section: Introductionmentioning
confidence: 99%